Tool use changes multisensory interactions in seconds: evidence from the crossmodal congruency task. - Holmes, N; Calvert, G; Spence, C (2007)
Active tool use in human and non-human primates has been claimed to alter the neural representations of multisensory peripersonal space. To date, most studies suggest that a short period of tool use leads to an expansion or elongation of these spatial representations, which lasts several minutes after the last tool use action. However, the possibility that multisensory interactions also change on a much shorter time scale following or preceding individual tool use movements has not yet been investigated. We measured crossmodal (visual-tactile) congruency effects as an index of multisensory integration during two tool use tasks. In the regular tool use task, the participants used one of two tools in a spatiotemporally predictable sequence after every fourth crossmodal congruency trial. In the random tool use task, the required timing and spatial location of the tool use task varied unpredictably. Multisensory integration effects increased as a function of the number of trials since tool use in the regular tool use group, but remained relatively constant in the random tool use group. The spatial distribution of these multisensory effects, however, was unaffected by tool use predictability, with significant spatial interactions found only near the hands and at the tips of the tools. These data suggest that endogenously preparing to use a tool enhances visual-tactile interactions near the tools. Such enhancements are likely due to the increased behavioural relevance of visual stimuli as each tool use action is prepared before execution.